Алгоритм регуляризации τ-метода Ланцоша и его реализация средствами алгебраического программирования - Денисенко, П.Н. (Кибернетика и системный анализ, 2011)
Побудовано алгебраїчний алгоритм для обчислення алгебраїчного многочлена yn порядку n є N в системах комп’ютерної алгебри. Цей многочлен апроксимує розв’язок y = y(x), x є [a, b], системи з лінійного диференцiального рiвняння з многочленними коефiцiєнтами та початкових умов в регулярнiй особливiй точцi нуль цього рiвняння оптимально в просторi Ck [a, b]. An algebraic algorithm is constructed for computing an algebraic polynomial yn of order n є N in computer algebra systems. This polynomial is an optimal approximation to the solution to y = y(x), x є [a, b] for a system of linear differential equations with polynomial coefficients and initial conditions at a special point of this equation in a space Ck [a, b].